ISOLATION OF LIMONOIDS FROM CLAUSENA EXCAVATA BURM.F AND THEIR ANTIBACTERIAL ACTIVITY AGAINST Enterococcus faecalis - Harizon, Harizon; Romundza, Febbry (LPPM Universitas Jambi, 2025)
This study aims to isolate and characterize limonoid compounds from Clausena excavata Burm.F and evaluate their antibacterial potential against Enterococcus faecalis, a pathogen associated with antibiotic resistance in healthcare settings. Plant samples were collected from natural habitats in Southeast Asia and identified by botanists for authenticity. The leaves, stems, and fruits were dried, ground into fine powder, and subjected to ethanol/methanol maceration, followed by liquid-liquid fractionation. Column chromatography and Thin Layer Chromatography (TLC) were used for initial compound separation, while High-Performance Liquid Chromatography (HPLC) was employed for further purification. Structural characterization was conducted using Nuclear Magnetic Resonance (NMR), Mass Spectrometry (MS), and Fourier Transform Infrared Spectroscopy (FTIR). The antibacterial activity of the isolated limonoids was tested against E. faecalis using the disk diffusion method, with Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) determined through broth microdilution assays. The results indicate that limonoid compounds from Clausena excavata exhibit moderate antibacterial activity, producing inhibition zones smaller than standard antibiotics but still demonstrating potential for bacterial growth suppression. This study highlights Clausena excavata as a promising natural source of antibacterial agents, contributing to alternative solutions against antibiotic-resistant bacteria. The findings support further exploration of limonoids as lead compounds for novel antimicrobial drugs, promoting the use of natural products in combating antibiotic resistance and advancing phytopharmaceutical applications in healthcare.